Psychometric properties of the multidimensional perfectionism scale in Mexican adults - Ortega Aguilar, Sikandar (2024)
The aim of this research was to review the psychometric properties of the Frost Multidimensional Perfectionism Scale(FMPS) in a non-clinical sample of 1,242 Mexican adults. The reliability and validity of the scale were assessed usingfactorial analyses, and Cronbach’s alpha (α) and McDonald’s omega (ω) indices were analyzed. The overall reliabilityof the scale was excellent (α = .928, ω = .928), with specific dimensions ranging from acceptable to excellent (concernover mistakes: α = .899, ω = .903; organization: α = .892, ω = .896). Exploratory factor analysis confirmed theadequacy of the data (KMO = .940, p < .001), with the final model fitting with five factors explaining 59.390% of thevariance. Confirmatory factor analysis yielded an RMSEA of .074, CMIN/DF of 7.882, GFI of .849, and CFI of .871,indicating acceptable but not excellent fit. These results suggest that the FMPS is a reliable and valid tool for assessingperfectionism in non-clinical Mexican adult populations. In clinical practice, the FMPS allows for a precise evaluationof perfectionism dimensions, enabling more specific and personalized diagnoses and treatments. Identifying specificareas such as concern over mistakes and organization can guide more effective therapeutic interventions. In conclusion,the FMPS is valuable for both academic research and clinical practice, providing a robust and adaptable tool for variouscultural and demographic contexts.